Sequence-dependent rotation axis changes in tennis. Issue 3 (3rd July 2017) - Hansen, Clint; Martin, Caroline; Rezzoug, Nasser; Gorce, Philippe; Bideau, Benoit; Isableu, Brice
Abstract: The purpose of this study was to evaluate the role of rotation axes during a tennis serve. A motion capture system was used to evaluate the contribution of the potential axes of rotation (minimum inertia axis, shoulder-centre of mass axis and the shoulder-elbow axis) during the four discrete tennis serve phases (loading, cocking, acceleration and follow through). Ten ranked athletes (International Tennis Number 1–3) repeatedly performed a flat service aiming at a target on the other side of the net. The four serve phases are distinct and thus, each movement phase seems to be organised around specific rotation axes. The results showed that the limbs' rotational axis does not necessarily coincide with the minimum inertia axis across the cocking phase of the tennis serve. Even though individual serving strategies were exposed, all participants showed an effect due to the cocking phase and changed the rotation axis during the task. Taken together, the results showed that despite inter-individual differences, nine out of 10 participants changed the rotation axis towards the minimum inertia and/or the mass axis in an endeavour to maximise external rotation of the shoulder to optimally prepare for the acceleration phase.